Ecological Quality Improvement of Urban Landscapes with Emphasis on Sustainable Development Principles Case Study: River of Darabad Valley, Tehran, Iran - Ahmadi, Ferial; Sadeghi, Ali Reza; Eskandarinezhad, Ali Reza (European Journal of Sustainable Development, 2016)
Sustainable development is known as a process that pave the way for achieving pleasant ecological quality in urban landscape. In fact, it seems that sustainable development principles and evaluation of the natural context should be the fundamental part in the process of improvement of the quality of urban landscape. The present research has been conducted in order to preserve and manage Tehran’s River of Darabad Valley landscape as a living, dynamic ecosystem; moreover, to improve the ecological quality of the riverbed through the implementation of sustainable development principles. Process recommendations to improve the ecological quality of the River of Darabad Valley through sustainable development are based on descriptive analysis of library research and case study, as well as observation procedures with survey studies. Recommendations have been based on the study and analysis of multiple primary factors, including environmental, cultural, physical, and social features. Subsequent suggestions for designing a sustainable landscape have been provided, and have been focused on repair and protection of the landscape, and ecological and aesthetic principles. Emphasis has been placed on protection and improvement of the natural landscape and the diverse bionetwork of the region, the removal of inappropriate applications and bio- environmental pollutants, and better rehabilitation and restoration of the context of valley’s river, as a human real and public space. Suggestions are in accordance with the natural limits of the river; serving to both protect the natural landscape of the river, and provide visitors with outdoor recreational experiences and areas, as well as welfare facilities. Key Words: Ecological quality, sustainable development principles, River of Darabad Valley